Essentials of managerial finance - Besley, Scott; Brigham, Eugene F. (Fort Worth : Harcourt Brace College Publisher, 2000)
Business
Keywords: Managerial finance; Fianancial management; Financial market; Financial institution; Capital budgeting; Capital management